Dissatisfaction about body image and associated factors: a study of young undergraduate students - Silva,Laleska Pâmela Rodrigues da (2019)
ABSTRACT Objective: To verify the prevalence of dissatisfaction with body image and its association with socio-demographic, economic, and anthropometric variables, as well as levels of physical activity among undergraduate students. Methods: A cross-sectional study was conducted with 348 undergraduate students at the dining hall of a public Brazilian university located in the state of Mato Grosso do Sul. Body image perception was evaluated using the Silhouette Matching Task. The other variables assessed were sex, age, marital status, housing conditions, socioeconomic class, weight, height, waist circumference and physical activity levels. Multinomial logistic regression was performed to verify the association between the dependent and independent variables. Results: Of the interviewees, 55.7% were men. The prevalence of dissatisfaction with body image was 59.8% among men and 55.2% among women. Dissatisfaction for being overweight, between men and women, was higher in overweight individuals when compared to normal weight individuals, according to the body mass index, and also higher in those at risk for cardiovascular disease when compared to those who were not at risk. The dissatisfaction for being thin was higher among women with low weight when compared to normal weight women, according to body mass index. There was no association between dissatisfaction for being thin and the variables analyzed among men. Conclusion: The prevalence of dissatisfaction with body image was observed in more than half of the individuals evaluated and is associated with nutritional status. Knowing the consequences of dissatisfaction with body image helps highlight the need for intervention strategies to avoid the practice of unhealthy behaviors.